The Correlation between Surface Tracking and Partial Discharge Characteristics on Pressboard Surface Immersed in MIDEL eN - Nur Amirah Othman; Hidayat Zainuddin; Aminuddin Aman; Sharin Abd Ghani; Imran Sutan Chairul (Institute of Advanced Engineering and Science, 2017)
This paper presents the investigation of the surface tracking on pressboard surface immersed in MIDEL eN oil. In this work, the development of surface discharge was analyzed by correlating the visual records of surface tracking on impregnated pressboard and the partial discharge (PD) activities. The PD activities during the surface tracking process were analyzed in terms of Phase Resolved Partial Discharge (PRPD) patterns. Throughout the experiment, surface discharge is found as the development of tree-like patterns in the form of white marks occurring on the oil-pressboard interface. This phenomenon is generally accepted as the drying out process that involves evaporation and decomposition of the oil molecules in the pressboard pores due to the surface discharge activities on the pressboard surface layer. The development of surface discharge on the pressboard surface can continue from minutes to months or even years until failure. Thus, condition monitoring system is important to characterize this type of faulty condition. The experimental results show that there is the decreasing trend of PD magnitude during the development of white mark hallway of a gap distance which is eventually suffered from an unexpected fault.